Summer in the city: behaviour of large gulls visiting an urban area during the breeding season. Issue 2 (2nd April 2016) - Huig, Naomi; Buijs, Roland-Jan; Kleyheeg, Erik
ABSTRACT: Capsule: Large numbers of Herring Gulls Larus argentatus and Lesser Black-backed Gulls Larus fuscus from a traditional colony in the Netherlands visit an urban area for food in the chick rearing period, causing nuisance while doing so. Aims: To assess the potential contribution of large gulls breeding in a traditional colony to gull–human conflicts in cities. Methods: Colour-ringed gulls from a nearby colony were counted in the study area throughout the 2014 breeding season. The average numbers observed daily per species and sex were compared between different breeding phases. Results: Fluctuations in numbers of both species could be explained by breeding phase. Numbers of females of both species and male Lesser Black-backed Gulls dropped significantly during laying and incubation. Numbers peaked post-hatching, coinciding with increased engagement in nuisance events and more frequent displacements within the study area. Conclusion: Large gulls from a traditional colony frequently visited the urban study area, especially when food demand for chick provisioning was high, suggesting that city visits are motivated by accessibility of urban food. The proportion of rooftop breeding gulls in this area is low. Therefore, measures to avoid nuisance should focus on reducing food availability rather than controlling gull breeding.